Screening Of Malaysian Patients With Nasopharyngeal Carcinoma (NPC) Using Comparative Genomic Hybridization (CGH) Technique For Identification Of Specific Genetic Alteration - Nor, Natasya Naili Muhamad (2012)
Nasopharyngeal Carcinoma (NPC) is a malignancy that originates from the epithelial lining of Fossa of Rosen Muller in the nasopharynx. It is a highly prevalent disease in Southern China and Southeast Asia including Malaysia. In this study, the genetic alterations from forty-four NPC patients from five hospitals in Malaysia were screened. Comparative Genomic Hybridization (CGH) technique was used for screening the genetic alterations. CGH is a molecular cytogenetic technique which is used to identify imbalanced genetic alterations that is present in this malignant disease.